1984
DOI: 10.2165/00003495-198428010-00002
|View full text |Cite
|
Sign up to set email alerts
|

Isotretinoin

Abstract: Isotretinoin is a new orally active retinoic acid derivative for the treatment of severe refractory nodulocystic acne. The pharmacological profile of isotretinoin suggests that it acts primarily by reducing sebaceous gland size and sebum production, and as a result alters skin surface lipid composition. Bacterial skin microflora is reduced, probably as a result of altered sebaceous factors. Isotretinoin 1 to 2 mg/kg/day for 3 to 4 months produces 60 to 95% clearance of inflammatory lesions in patients with sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(23 citation statements)
references
References 92 publications
0
22
0
Order By: Relevance
“…Oral isotretinoin at a dose of 0.5-2.0 mg/kg/day[3] reduces sebaceous gland activity within 6 weeks[4] of starting therapy. Isotretinoin induces a dose-dependent decrease in size and cross-sectional area of sebaceous glands; dose-dependent reduction in sebum production; sebocyte apoptosis[56] and histological changes, such as lobular collapse, follicular atrophy and greater preponderance of undifferentiated acinar cells. Augmented production of neutrophil gelatinase associated lipocalin[7] in the skin by isotretinoin has been correlated with human sebocyte apoptosis within sebaceous glands, which leads to decreased production of sebum within the sebaceous glands and lobular collapse.…”
Section: Discussionmentioning
confidence: 99%
“…Oral isotretinoin at a dose of 0.5-2.0 mg/kg/day[3] reduces sebaceous gland activity within 6 weeks[4] of starting therapy. Isotretinoin induces a dose-dependent decrease in size and cross-sectional area of sebaceous glands; dose-dependent reduction in sebum production; sebocyte apoptosis[56] and histological changes, such as lobular collapse, follicular atrophy and greater preponderance of undifferentiated acinar cells. Augmented production of neutrophil gelatinase associated lipocalin[7] in the skin by isotretinoin has been correlated with human sebocyte apoptosis within sebaceous glands, which leads to decreased production of sebum within the sebaceous glands and lobular collapse.…”
Section: Discussionmentioning
confidence: 99%
“…The action of isotretinoin was supported by numerous publications that led to hypothesize that some pharmacokinetic properties result in the specific targeting of sebaceous glands in reducing its size and sebum production [348,349]. Isotretinoin is actually considered as the most potent inhibitor of sebum production.…”
Section: From Vitamin a To Isotretinoin: Innovative Views On Acne Patmentioning
confidence: 99%
“…The severity of malformation depends on the dose and embryonic stage at the time of drug administration [11, 15-17]. The 13-cis-RA or Acccutane ® is a retinoic acid derivative that poses several benefits such as treating severe cystic acne [18]. However, the clinical observations strongly have suggested that the 13-cis-RA is a human teratogen.…”
Section: Introductionmentioning
confidence: 99%